The Effect of Giving Warm Water on Reducing Nausea and Vomiting in Pregnant Women at the Kumita Sari Clinic, Kec. Padang Tualang District. Langkat Year 2020 - Aisyah (Science Midwifery, 2022)
Pregnancy is a change in order to continue offspring naturally, resulting in a fetus growing in the mother's womb. Pregnancy involves physical and emotional changes from the mother as well as social changes in the family. Nausea and vomiting are complaints that are often experienced by pregnant women, especially in the first trimester. Symptoms usually appear at 7-12 weeks of gestation. General Purpose To determine the effect of giving warm water to reduce nausea and vomiting in pregnant women at the Kumita Sari Clinic, Kec. Tualang District. Langkat in 2020. The results of hypothesis testing to see the relationship between variable X and variable Y are with a significant level (α) = 5% (0.05) and df = 1, the results are p.value = 0.000 at df = 1 where sig < (0.000 < 0.05) then it can be seen that there is an effect of giving warm water to the reduction of nausea and vomiting in pregnant women at the Kumita Sari Clinic in 2020